Bialet Masse. Cultural heritage and local identity. An interdisciplinary investigation - Cantoni, Juan Carlos (Centro de Estudios de Arqueología Histórica (CEAH) de la Universidad Nacional de Rosario, 2023)
This paper consists of presenting results and methodological proposals linked to the experiences carried out in the recovery of tangible and intangible heritage that confers an identity character to the town of Bialet Massé, Province of Córdoba. It seeks to advance from the biographical construction of the cha- racter in the framework of collaborative research with the archaeological recovery of his most important work: his Primera Argentina lime factory and on that basis reflect on the interdisciplinary nature of historical archaeology. The activities carried out come from the interdisciplinary project “Bialet Massé. Cultural heritage, tourism development and local identity” (Framework Agreement for Assistance and Cooperation entered into between the Municipality of Bialet Massé and the Faculty of Applied Sciences for the Systematic Study of Tourism and Population of the University of Morón- 2000-2004).